2003
DOI: 10.1007/s00410-003-0445-2
|View full text |Cite
|
Sign up to set email alerts
|

Rutile/TiO2II phase equilibria

Abstract: The transition between rutile and a-PbO 2 structured TiO 2 (TiO 2 II) has been investigated at 700-1,200°C and 4.2-9.6 GPa. Hydrothermal phase equilibrium experiments were performed in the multi-anvil apparatus to bracket the phase boundary at 700, 1,000, and 1,200°C. The equilibrium phase boundary is described by the equation: P (GPa)=1.29+0.0065 T (°C). In addition, growth of TiO 2 II was observed in experiments at 500 and 600°C, although growth of rutile was too slow to bracket unambiguously the equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 18 publications
2
51
0
Order By: Relevance
“…The difference in chemical composition between the C-rich nitrogen isotope standards and the Ti-rich, C-poor TiN raises a potential concern over the accuracy of the mass-dependent fractionation correction. Although a full evaluation requires a TiN standard with welldetermined 15 N/ 14 N, the absence of significant variations in instrumental mass-dependent fractionation for a variety of N-bearing materials supports the approach followed here. Data were processed as quantitative isotopic ratio images by using custom software (L'image; L. Nittler, Lawrence Livermore National Laboratory) and were corrected for detector dead time and image shift from layer to layer.…”
Section: Methods and Analytical Techniquesmentioning
confidence: 77%
See 2 more Smart Citations
“…The difference in chemical composition between the C-rich nitrogen isotope standards and the Ti-rich, C-poor TiN raises a potential concern over the accuracy of the mass-dependent fractionation correction. Although a full evaluation requires a TiN standard with welldetermined 15 N/ 14 N, the absence of significant variations in instrumental mass-dependent fractionation for a variety of N-bearing materials supports the approach followed here. Data were processed as quantitative isotopic ratio images by using custom software (L'image; L. Nittler, Lawrence Livermore National Laboratory) and were corrected for detector dead time and image shift from layer to layer.…”
Section: Methods and Analytical Techniquesmentioning
confidence: 77%
“…At temperatures appropriate for mantle upwelling at ocean spreading centers, TiO 2 II is stable only at pressures within the stishovite stability field (Ͼ10 GPa) (15). Nevertheless, neither the TiO 2 II nanoinclusions nor the host coesite show any evidence of reaction to their low-pressure polymorphs, rutile and quartz, respectively.…”
Section: How Great Might the Depth Of Origin Be?mentioning
confidence: 99%
See 1 more Smart Citation
“…Rutile transforms to TiO 2 -II at 4-12 GPa and 400-1500°C [3], 10 GPa and 400°C [4], 4.6-8.5 GPa and 500-900°C [5], 4.5-7.5 GPa and 600-1100°C [6], 4.2-9.6 GPa and 700-1200°C [7]. It appears that the phase transition of rutile to TiO 2 -II involve some thermal activation process.…”
Section: Discussionmentioning
confidence: 99%
“…i  - had been firstly synthesized by static compression experiment [3]. A number of static compression experiments succeed in the transition of rutile to TiO 2 -II at pressure range between 4 and 12 GPa and temperature between 400 and 1500°C [3][4][5][6][7]. Shock-loading experiments revealed that rutile transforms to i  - at peak shock pressure from 20 to 100 GPa [8][9][10].…”
mentioning
confidence: 99%